Differentiation of Leptomeningeal and Vascular Enhancement on Post-contrast FLAIR MRI Sequence: Role in Early Detection of Infectious Meningitis - Ahmad, Armeen (J Clin Diagn Res, 2015)
Objective: To qualitatively and quantitatively differentiate leptomeningeal and vascular enhancement on Post-contrast Fluid Attenuated Inversion Recovery (PCFLAIR) sequence compared to post-contrast T1-weighted (PCT1W) sequence with fat suppression (FS) and evaluate its role in early detection of infectious meningitis. Materials and Methods: Thirty-one patients with diagnosis of meningitis were evaluated with pre and post-contrast FLAIR and T1-weighted sequences with fat suppression (FS). Qualitative assessment was done by two observers for presence, absence or equivocal status of leptomeningeal enhancement. Further, quantitative estimation of single pixel signal intensities (SPSI) for meningeal and vascular enhancement was undertaken. A statistical comparison was performed using Kappa coefficient and t-test. Results: The overall qualitative accuracy was 90.3% for PCFLAIR compared to 54.8% for PCT1W with FS sequence. PCFLAIR was found to be 100% accurate in the detection of tubercular and pyogenic meningitis and 70% accurate in the detection of viral meningitis while PCT1W with FS sequence showed the corresponding accuracy to be 76.2% and 0% respectively. Both observers rated PCFLAIR images better than PCT1W with FS at detecting meningitis (p<0.05). The quantitative assessment revealed that the SPSI difference between the average meningeal and vascular enhancement on PCFLAIR was significantly greater than that on PCT1W with FS sequence (t= 6.31, p<0.01). Conclusion: PCFLAIR sequence has insignificant component of vascular enhancement compared to meningeal enhancement. This makes meningeal inflammation easily discernable and aids in early detection of infectious meningitis.